The Almajiri System and Insurgency in the Northern Nigeria: A Reconstruction of the Existing Narratives for Policy Direction - Usman, Abbo; Mohd. Zain, Zawiyah; Njidda, Bashir A (International Journal Corner, 2017)
The Almajiri phenomenon represents one of the messy and wicked problem thwarting the policy maker’s effort of addressing the problems of youth restiveness, disaffectedness and insurgency in Northern Nigeria. While there is lack of empirical studies on the linkage between the Almajiri system and violence in Northern Nigeria, three conflicting narratives on the issue exists which instead of unrevealing the dilemma has further throw the policy makers into conundrum. While the first narrative has it that the Almajiri system in itself is an instrument of youth radicalization. The second narrative argued that such claims are rather flawed and problematic. The third narrative argued that relative deprivation and destitution are the main causes of radicalization among Almajiri. This work therefore intends to put the issue into proper perspective by providing a balance argument based on empirical evidence. The work employs an ethnographic design where qualitative data were generated through interviews and focus group discussions. It is the contention of this work that, though the Almajiri system in itself does not radicalize the Almajirai cohort but so many decades of bad governance have invariably transformed it into a mechanism for the production of jobless, traumatized and alienated large youth cohort who apparently becomes the target for recruitment by the insurgence leaders. The work concludes by suggesting a policy direction and implication.